1974
DOI: 10.1128/aem.28.4.628-637.1974
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal Enterotoxin B and Nuclease Production Under Controlled Dissolved Oxygen Conditions

Abstract: Enterotoxin B, nuclease, and total exoprotein production by Staphylococcus aureus strain S-6 was studied in a 0.5-liter fermentor system. While these extracellular products were elaborated over a wide range of aeration rates, maximal production occurred within the very narrow range of 125 to 150 cm3 of air per min. The levels attained at the optimal aeration rate were not increased by maintaining a constant pH, although yield of enterotoxin:cell mass was highest at a constant pH of 7.0. During the growth cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1976
1976
1993
1993

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…aureus 100 and Staph. aureus 56, respectively (Carpenter & Silverman 1974;Carpenter & Silverman 1976;Jarvis et al 1973) where both aeration rate and dissolved oxygen concentration were found to affect the formation of each toxin as well as nuclease and total extracellular protein.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…aureus 100 and Staph. aureus 56, respectively (Carpenter & Silverman 1974;Carpenter & Silverman 1976;Jarvis et al 1973) where both aeration rate and dissolved oxygen concentration were found to affect the formation of each toxin as well as nuclease and total extracellular protein.…”
Section: Discussionmentioning
confidence: 98%
“…1) or whether some other factor such as the accumulation of a particular metabolite in response to certain aeration conditions, or a volatile inhibitor (such as carbon dioxide) was responsible for the effects observed. It is interesting to note, however, that the observations of Dietrich et al (1972) on the effect of shaking speed on the secretion of enterotoxin B were explained by the discovery that both an optimum aeration rate and dissolved oxygen concentration were required for enterotoxin B production (Carpenter & Silverman 1974).…”
Section: Discussionmentioning
confidence: 99%
“…1. The fermentor, with attendant equipment for temperature and aeration regulation has been previously described (4).…”
Section: Methodsmentioning
confidence: 99%
“…The degree of aeration and DO level have been shown to influence the production of other staphylococcal products. Carpenter and Silverman (5) observed that maximal enterotoxin B (SEB) production occurred within a narrow range of aeration rates (125 to 150 cm3/min). A constant DO of 100% resulted in profuse growth but no SEB or nuclease was produced, whereas 10% stimulated synthesis of both products.…”
mentioning
confidence: 99%